Transformation Of The Traditional Dance Choreography Of Molapi Saronde Gorontalo - Siska Udilawaty; Sari Hunowu, Risti Puspita (UNIVERSITAS STEKOM, 2022)
This study discusses the change in the choreography of the traditional Molapi Saronde dance to the Saronde Kreasi dance in the city of Gorontalo. This research will focus on the changes that occur in the choreography of the Molapi Saronde dance, the creation of the Saronde dance, because along with the times, the dance which was usually only performed at traditional weddings among kings (nobles) has now become a public dance that can be held for entertainment events such as welcoming guests. The purpose of this research is to find out the changes that exist in the traditional Molapi Saronde dance to the creation of the Saronde dance and to analyze further about the changes in the choreographic movement of the Molapi Saronde dance related to the traditional values ​​that exist in Gorontalo. this research is qualitative. Benefits This research provides new knowledge to the millennial generation and tourists who want to know the meaning of each choreographic change in the Molapi Saronde dance and the Saronde Kreasi dance. The results of this study determine the changes and differences in the traditional dance from the Molapi Saronde to the Saronde Kreasi dance.